Global Research Trends on the Use of Nanotechnology to Boost Meat Production: A Scientometric Analysis - Idamokoro, Emrobowansan Monday; Hosu, Yiseyon Sunday (Frontiers in Research Metrics and Analytics, 2022)
Meat production play a vital socio-economic role for sustainable development and for promoting food security in most countries. However, not much is known about research agendas done globally and the advancement of knowledge-generating networks in this area of study. The present study aims to reveal and analyse scientific research outputs on meat production linked with recent nanotechnology research work done till date. A compilation of research advancement and development within the sphere was realized through a scientometric study to comprehend the trend of research outputs, scientific impacts, authors’ involvement, collaboration networks, and the advancement of knowledge gaps for future research endeavours on the current subject matter. Scholarly published articles were retrieved from the web of science (WOS) and Scopus databases from 1985 to 2020 and they were merged together using bibliometric package in R studio. All duplicated articles (438) from both data bases were excluded. A combination of terms (nano* AND ( livestock* OR meat* OR beef* OR mutton* OR pork* OR chevon* OR chicken* OR turkey* )), and conversely analyzed for scientometric indices. A collection of 656 peer-reviewed, research articles were retrieved for the study period and authored by 2133 researchers with collaboration index of 3.31. Research outputs was highest in the year 2020 with total research outputs of 140 articles. The topmost three authors’ keywords commonly used by authors were nanoparticles, meat and chitosan with a respective frequency of 75, 62 and 57. China, Iran and India ranked top in terms of meat production research outputs linked to nanotechnology, and total citation with respective article productivity (total citations) of 160 (3193), 111 (1765), and 37 (552). Our findings revealed an increasing trend in research (with an annual growth rate of 25.18 %) tending towards advancing meat production with the use of nanotechnology. Likewise, there is an increasing pointer to the fact that research work on nanotechnology and meat production has the prospect to influence positively, decision making on research direction, and collaborations, hereby increasing the production of meat and its products in the future.